Training Effectiveness and Trainee Performance in a Voluntary Training Program: Are Trainees Really Motivated?. (December 2014) - Huang, Yunchen; Strawderman, Lesley; Babski-Reeves, Kari; Ahmed, Shaheen; Salehi, Arash
Effective training programs are critical for successful employee performance. The same can be said for volunteer programs. Volunteers need to have the knowledge and skills necessary to fulfill the mission of the organization. In this study, we examine the impact of training methods and trainees' demographic factors on the effectiveness of a training program for a voluntary program. Survey results ( N = 5, 727) indicate a very low percentage of participation (16.46%) in the voluntary program after training. Responses also indicate that content knowledge recall after training is affected by training year (the year receiving training), industrial sector, calling history, and training delivery method. Participants' desires for retraining are also impacted by the type of training received, the industry sector, as well as past participation in the program. Recommendations for voluntary training programs based on study results and future research directions are presented.